Design of an Exoskeleton based on Four Cases of Upper Limb Rehabilitation Study - Cruz-Martínez, G. M.; Vilchis-González, A. H.; Zúñiga-Avilés, L. A.; Ávila-Vilchis, J. C.; Hernández-Sánchez, A. I. (Revista Mexicana de Ingenieria Biomedica, 2018)
This paper presents an approach for passive upper limb rehabilitation based on four case studies by analyzing the pathologies and exercises that are applied. To carry out the experimentation in the proposed cases, the data from the trajectories of the patient’s arm articulations were registered, performing the rehabilitation exercises with a therapist. The ERMIS exoskeleton ́s seven degrees of freedom was designed to emulate the anatomical movements in the arm during rehabilitation from the requirements of the case studies. To validate the exoskeleton performance in the study cases, the ERMIS’s dynamic model was simulated and the data were compared with the sampled data of the exercises. At the end, the results obtained from exoskeleton exercises emulating rudder therapy, where shoul-der, elbow and wrist movements were showed with an accuracy of 95%.